Normality in products of Rudin's Dowker spaces which are constructed from Suslin trees - Kasai, Yosuke (Topology Proceedings, 2023)
If $κ$ is the successor of an uncountable regular cardinal, $N$ a finite integer and $\left\{R^i\right\}_{i \in N}$ is a finite sequence of $κ$-Suslin trees such that $\prod_{i \in N} R^i$ has the $κ$-c.c., then $\prod_{i \in N} X^i$ is normal when $X^i$ is a Rudin's Dowker space that is constructed from $R^i$. Moreover, $\prod_{i \in N} X^i$ is again Dowker by the same assumption.